Change in neighborhood environments and depressive symptoms in New York City: The Multi-Ethnic Study of Atherosclerosis. (March 2015) - Mair, C.; Diez Roux, A.V.; Golden, S.H.; Rapp, S.; Seeman, T.; Shea, S.
Abstract: Physical and social features of neighborhoods, such as esthetic environments and social cohesion, change over time. The extent to which changes in neighborhood conditions are associated with changes in mental health outcomes has not been well-established. Using data from the MultiEthnic Study of Atherosclerosis, this study investigated the degree to which neighborhood social cohesion, stress, violence, safety and/or the esthetic environment changed between 2002 and 2007 in 103 New York City Census tracts and the associations of these changes with changes in depressive symptoms. Neighborhoods became less stressful, more socially cohesive, safer, and less violent. White, wealthy, highly educated individuals tended to live in neighborhoods with greater decreasing violence and stress and increasing social cohesion. Individuals living in neighborhoods with adverse changes were more likely to have increased CES-D scores, although due to limited sample size associations were imprecisely estimated ( P >0.05). Changes in specific features of the neighborhood environment may be associated with changes in level of depressive symptoms among residents. Highlights: Between 2002 and 2007, neighborhoods in New York City changed. Neighborhoods became less stressful, more socially cohesive, safer, and less violent. White, rich, highly educated people lived in more rapidly improving neighborhoods. High SES areas had greater improvements in social cohesion and violence reduction. Increasing neighborhood social cohesion was associated with decreasing depression.